The Cell Type–Specific Functions of miR-21 in Cardiovascular Diseases - Dai, Beibei; Wang, Feng; Nie, Xiang; Du, Hengzhi; Zhao, Yanru; Yin, Zhongwei; Li, Huaping; Fan, Jiahui; Wen, Zheng; Wang, Dao Wen; Chen, Chen (Frontiers in Genetics, 2020)
Cardiovascular diseases are one of the prime reasons for disability and death worldwide. Diseases and conditions, such as hypoxia, pressure overload, infection, and hyperglycemia, might initiate cardiac remodeling and dysfunction by inducing hypertrophy or apoptosis in cardiomyocytes and by promoting proliferation in cardiac fibroblasts. In the vascular system, injuries decrease the endothelial nitric oxide levels and affect the phenotype of vascular smooth muscle cells. Understanding the underlying mechanisms will be helpful for the development of a precise therapeutic approach. Various microRNAs are involved in mediating multiple pathological and physiological processes in the heart. A cardiac enriched microRNA, miR-21, which is essential for cardiac homeostasis, has been demonstrated to act as a cell–cell messenger with diverse functions. This review describes the cell type–specific functions of miR-21 in different cardiovascular diseases and its prospects in clinical therapy.